Mycobacterium avium subsp. paratuberculosis in Colombia (1924-2016): a review - Nathalia Correa-Valencia (Universidad de Antioquia, 2018)
Mycobacterium avium subsp. paratuberculosis (MAP) is an acid-fast, gram-positive bacillus. MAP is the causal agent of paratuberculosis (PTB) or Johne’s disease, an infectious disease affecting domestic ruminants and some wild species. Its importance as a potentially zoonotic agent due to its relation to Crohn’s disease (CD) in humans is still under debate and investigation. The aim of the present systematic review is to summarize original studies on MAP carried out in Colombia since 1924, as well as to establish strengths, weaknesses, and future research opportunities in the country with emphasis on diagnosis and epidemiology. The initial search for existing publications reporting original studies on MAP, PTB, and the relationship between MAP and CD was carried out in the available databases and national libraries. After compilation of the available studies (n = 20), the relevant data was extracted (year, province of report, species studied, diagnostic tests used, study design, summary of results, and authors). Recommendations for future research opportunities on MAP in Colombia are made.